Application of a marker of ciliated epithelial cells to gynaecological pathology. Issue 5 (1st May 1999) - Comer, M T; Andrew, A C; Leese, H J; Trejdosiewicz, L K; Southgate, J
Abstract : BACKGROUND: The assessment of neoplastic disease in gynaecological histopathology can be complicated by the high incidence of metaplasia seen in tissues of the female genital tract. There is a need to identify specific tissue markers which can be applied in routine histopathological practice. AIM: To examine the clinical potential of a monoclonal antibody, LhS28, which reacts with basal bodies of ciliated epithelial cells. METHODS: A panel of normal and pathological gynaecological tissues was processed and labelled with LhS28. RESULTS: LhS28 immunoreactivity was found in the normal Fallopian tube where it was confined to ciliated rather than secretory epithelial cells. In the remaining specimens, LhS28 was associated exclusively with ciliated cells in tubal metaplasias of the cervix and endometrium and in benign serous lined inclusion cysts. CONCLUSIONS: LhS28 may be a valuable marker for identifying metaplasia of tubal type and may find application in distinguishing tubal metaplasia from low grade cervical glandular intraepithelial neoplasia.